George Frederick Bristow - Preston, Katherine K. (American composers., 2020)
"As American classical music struggled for recognition in the mid-nineteenth century, George Frederick Bristow emerged as one of its most energetic champions and practitioners. Katherine K. Preston explores the life and works of a figure admired in his own time and credited today with producing the first American grand opera and composing important works that ranged from oratorios to symphonies to chamber music. Preston reveals Bristow's passion for creating and promoting music, his skills as a businessman and educator, the respect paid him by contemporaries and students, and his tireless work as both a composer and in-demand performer. As she examines Bristow against the backdrop of the music scene in New York City, Preston illuminates the little-known creative and performance culture that he helped define and create. Vivid and richly detailed, this book enriches our perceptions of musical life in nineteenth-century America"--